Isolation and study of bioactivities study of the recombinant human endostatin - E. S. Kalinina; N. V. Pozdniakova; D. A. Korzhenevsky; N. B. Feldman; S. V. Lutsenko; V. I. Shvets (Тонкие химические технологии)
A novel technique has developed to isolate recombinant human endostatin from cultured e. coli cells. endostatin was incorporated into liposomes and such liposomes were tested cytotoxic activity in vitro and for antitumor activity in vivo